Pengaruh Penambahan Butanol Pada Bahan Bakar Solar Terhadap Karakteristik Pembakaran Single Droplet - Brahmantyo Luqman Sayoko; Radissa Dzaky Issafira (Politeknik Negeri Padang, 2024)
Dependence on fossil fuels is one of the most serious threats to the global environment. In addition, petroleum reserves are also decreasing. Meanwhile, the level of oil consumption is always increasing to meet the demand for fuel. Economical and sustainable alternative energy solutions are essential to meet the growing global energy demand without compromising environmental sustainability. One type of alternative fuel that shows very promising potential is biofuel, especially biodiesel. Biodiesel has potential as a more environmentally friendly alternative to diesel fuel, but its low combustion rate and higher viscosity compared to conventional diesel fuel present technical challenges that need to be overcome. The different chemical properties of butanol from biodiesel allow it to have a positive impact on combustion characteristics, such as viscosity, flash point, heating value, and combustion rate. The combustion characteristics that will be studied in this research using single droplet combustion testing include droplet visualization to measure the dimensions of the flame, temperature during the combustion process recorded by a thermocouple, data logger, and video recording during the combustion process to obtain information regarding the ignition delay value. The test steps were repeated five times for each fuel variation and then averaged. In this study, the samples tested included pure diesel, diesel blend with 10% butanol, diesel blend with 20% butanol, diesel blend with 30% butanol, diesel blend with 40% butanol and diesel blend with 50% butanol. From this study, the visualization of the flame is obtained, where the combustion of pure diesel oil droplets has a higher and wider flame, while the flame of the butanol diesel mixture produces a flame whose maximum height is lower than pure diesel oil. The ignition delay time of pure diesel oil is greater than the ignition delay time of the diesel butanol blend. In addition, the maximum combustion temperature produced by each blend is different